An Analysis of Loan Loss Provisioning Behaviour in Chinese Banks - ZHU, Yidan (2017)
Loan loss provision (LLP) of commercial banks is used to resist the loan risk and drew for compensating the future loan losses, which is extracted based on assessment of loan loss reserves. It is of great significance to the sound management of banks. The efficiency of LLP refers to the validity of LLP decision-making in banks when they intend to improve the quality of assets, cover the maximum credit losses and control the credit risk in banks under the existing technical level, namely the proximity of LLP decision-making to the optimal frontier. This study chooses 37 listed commercial banks in China during the 2011-2016 time period as the study object, using the stochastic frontier production function model in the empirical analysis of China's commercial banks LLP provision efficiency and its affecting factors. Our results indicate that drawing LLP in large, low non-interest income and low non-interest expense banks is more efficient. Besides, LLP in Chinese banks is significant procyclical, and surprisingly the efficiency of LLP decision-making does not increase over time.